Water permeability/impermeability in seeds of 15 species of Caragana (Fabaceae) - Chen, Dali; Zhang, Rui; Baskin, Carol C.; Hu, Xiaowen (PeerJ, 2019)
Majority legumes in the temperate and arctic zones have water-impermeable seeds (physical dormancy, PY). However, various authors have reported that seeds of some Caragana species are water-permeable and thus non-dormant. We (1) tested seeds of 15 species of Caragana matured in the same site in 2014, 2016 and/or 2017 for presence of PY, (2) determined if dry storage decreased or increased the percentage of seeds with PY and (3) located the site on the seed coat of 11 species where water enters the seed. Sixty-three percent and 45% of the seeds of C. roborovskyi had PY in 2016 and 2017, respectively, but only 0–14% of the seeds of the other 14 species had PY. The palisade layer in the seed coat of water impermeable seeds had no cracks in it, whereas cracks were present in the palisade layer of water-permeable seeds. Year of collection and dry storage had significant effects on imbibition of two species (C. acanthophylla and C. roborovskyi). In two (C. acanthophylla and C. roborovskyi) of the 11 species tested, the hilum was the site of water entry into seeds (control seeds, not any dormant broken treatments), but for the other nine species tested water entered through all parts of the seed coat.
Keywords: Seed coat structure; Hardseededness; Imbibition; Caragana; Maternal environment; Seed storage